2021
DOI: 10.1080/21645515.2021.1938921
|View full text |Cite
|
Sign up to set email alerts
|

Uncertainty and unwillingness to receive a COVID-19 vaccine in adults residing in Puerto Rico: Assessment of perceptions, attitudes, and behaviors

Abstract: Background: Widespread vaccination against COVID-19 is essential to control the pandemic. Estimates of unwillingness and uncertainty toward COVID-19 vaccination and factors associated with it remain unclear among adults in Puerto Rico (PR). Objective: To examine factors associated with uncertainty and unwillingness of COVID-19 vaccination among adults in PR. Methods: The Health Belief Model was used to develop an online survey. Analyses included adjusted logistic regressions (aOR). A total of 1,911 adults comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 25 publications
(65 reference statements)
1
19
0
Order By: Relevance
“…After the elimination of duplicate studies, we assessed the titles and abstracts of the 434 remaining studies, and 401 articles were eliminated because they did not match the selection criteria. A total of 33 studies were read in full-text and 19 studies were included in the qualitative synthesis and 18 in the quantitative synthesis [ 10 , 13 , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] ]. We did not include the study of Villareal-Garza et al in the meta-analysis of non-pregnant women, because the study population was specifically women with breast cancer whereas the population of the remaining articles was made up of individuals without a specific pathology.…”
Section: Resultsmentioning
confidence: 99%
“…After the elimination of duplicate studies, we assessed the titles and abstracts of the 434 remaining studies, and 401 articles were eliminated because they did not match the selection criteria. A total of 33 studies were read in full-text and 19 studies were included in the qualitative synthesis and 18 in the quantitative synthesis [ 10 , 13 , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] ]. We did not include the study of Villareal-Garza et al in the meta-analysis of non-pregnant women, because the study population was specifically women with breast cancer whereas the population of the remaining articles was made up of individuals without a specific pathology.…”
Section: Resultsmentioning
confidence: 99%
“…The present study was a secondary analysis that used data from a previously described cross-sectional study [ 19 ]. In summary, an anonymous web-based questionnaire was conducted in Puerto Rico and collected data through a convenience sampling approach.…”
Section: Methodsmentioning
confidence: 99%
“…Understanding how religiosity is associated with HBM constructs in the context of COVID-19 vaccination may help create effective vaccination campaigns. Previous studies, including one in Puerto Rico, have shown that HBM constructs including lower perceived COVID-19 susceptibility and severity, less perceived vaccination benefits, and more barriers contribute to lower vaccination intent [ 17 , 19 ]. Additionally, these studies documented that specific cues to action significantly impacted vaccination intent [ 17 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, there are countries with very low vaccination rates, either for economical, logistical, or individual reasons. [12][13][14][15] As the new infections continue throughout world, emergence of novel variants of concern (VOC) such as the delta [16] or the omicron variants, [17] is inevitable. Even single mutations found in new variants may increase the pathogenicity and transmissibility of the virus and reduce the effects of vaccines.…”
Section: Introductionmentioning
confidence: 99%